PEMBAHARUAN PENYELESAIAN PERSELISIHAN KETENAGAKERJAAN DI PENGADILAN HUBUNGAN INDUSTRIAL BERDASARKAN ASAS SEDERHANA, CEPAT DAN BIAYA MURAH SEBAGAI UPAYA PELAKSAAN KEPASTIAN HUKUM DAN KEADILAN - Yeti Kurniati; Dhanang Widijawan; Paulana Christian Suryawin; Muhammad Raihan Firdaus; Eti Haryati; Erid Gauri Putra (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The settlement of industrial relations disputes in labor law after the enactment of Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes is known as a voluntary settlement model through bipartite, conciliation, mediation, and arbitration; and a mandatory settlement model, namely through the Industrial Relations Court. The existence of the Industrial Relations Court raises problems, both the knowledge of workers/laborers about formal law and material labor law, long processes, and inadequate legal substance. Problems regarding the settlement of industrial relations disputes can consist of many factors, namely disputes regarding rights, disputes of interest, disputes of rights, disputes over termination of employment and disputes between trade unions/labor unions in one company, in addition to that also regarding the competence of the Industrial Relations Court so that it cannot effectively resolve labor disputes. This research uses a normative juridical research approach. Considering that this research is normative legal research, the approach used is a normative juridical approach based on the study of positive law, namely Law No. 2 of 2004 and to examine the principles of justice. The research results identified several weaknesses, both in terms of legal structure and substance in the renewal of Industrial Relations Dispute Settlement in the Industrial Relations Court. Efforts to overcome this by reforming the settlement process in the Industrial Relations Court, namely by establishing a PHI in each District Court, Regency/City. The revision of Law No. 2 of 2004 is considered unable to accommodate and does not reflect the principles of simplicity, speed and low cost in the trial process in the Industrial Relations Court.